Development of Flipbook-Based Learning Media at SMK Negeri 66 Jakarta on Vegetable Cutting Techniques Material - Rizki Fawzan Zulfi; Rina Ferbriana; Soeprijanto Soeprijanto (PT. Anagata Sembagi Education, 2025)
This study aims to develop a flipbook-based learning medium to enhance the understanding and skills of vocational high school (SMK) students majoring in Culinary Arts, specifically on the topic of vegetable cutting techniques. This fundamental skill is essential in cooking practice, yet there is a lack of effective and engaging learning media available in schools. The study adopts the DDD-E development model to design, produce, and evaluate the flipbook-based learning medium on vegetable cutting techniques for culinary students. The development process includes expert validation, user testing, and both qualitative and quantitative data analysis to assess the feasibility and effectiveness of the media. The results show that the flipbook learning media developed using the DDD-E model is highly suitable for use in Culinary Basics instruction, with validation scores of 98% from subject matter experts, 98% from media experts, and 86% from language experts. The media was developed using Heyzine and Canva Pro applications, incorporating a combination of text, images, videos, audio, and interactive exercises. It underwent one-to-one, small group, and field testing stages, all of which received very positive responses in terms of appearance, ease of use, and learning effectiveness.